Use of brightness wavelet transformation for automated analysis of serum metallothioneins‐ and zinc‐containing proteins by Western blots to subclassify childhood solid tumours. Issue 11 (26th April 2013) - Vyslouzilova, Lenka; Krizkova, Sona; Anyz, Jiri; Hynek, David; Hrabeta, Jan; Kruseova, Jarmila; Eckschlager, Tomas; Adam, Vojtech; Stepankova, Olga; Kizek, Rene
Abstract : In this study, we determined serum levels of metallothioneins (MTs) and zinc in children with solid tumours (neuroblastoma, Hodgkin lymphoma, medulloblastoma, osteosarcoma, Ewing sarcoma and nephroblastoma) by differential pulse voltammetry Brdicka reaction and ELISA. Zn(II) level in patients sera was 40% compared to controls, contrariwise, MT level was 4.2 × higher in patients. No significant differences among single diagnoses were found both for Zn(II) and MT. When determined Zn(II)/MT ratio, in controls its value was 24.6, but it was 2.6 in patients. After Western‐blotting with anti‐MT and anti‐Zn chicken antibodies, variable intensities of the bands within the samples were observed. The brightness curve obtained for each sample both for MT‐ and Zn blots was further analysed to produce a list of band positions together with some complementary information related to the intensity of the observed bands by the optimised algorithm. We constructed from those profiles decision trees that enable to distinguish different groups of tumours. The blood samples were heat‐treated, in which we supposed mainly MT, but samples contained other thermostable Zn‐containing proteins that were helpful for identification of embryonal tumours with 88% accuracy and for identification of sarcomas with 78% accuracy. In MT blots the accuracies were 53 and 45%, respectively. Simultaneous analysis of MT and Zn blots did not increased accuracy of identification neither in embryonal tumours (80%) nor in sarcomas. Those results are promising not only from diagnostic point of view but particularly in the area of studying of individual MT isoforms and their aggregates in malignant tumours.